The source of income from the sale of goods electronically: an analysis of the division of the taxing rights in cross-border solutions - Harnekar, Zafar (Department of Finance and Tax, 2016)
The digital economy is rapidly evolving and changing the way businesses operate. This is as a result of the increased use and reliance of technologies in business processes. As more companies adopt technology in their operations and as technology is continually developing, it becomes cheaper to implement technology in business processes over time. Traditional tax principles, domestic and international are reliant on some level of physical activity being performed in a country before the taxing right is granted. In the past, businesses required a level of physical presence in each country they operated in, in order to generate a significant level of economic activity. However, through the use of technology, businesses are now able to centralise their core business functions by operating on a global or regional level, and thereby foregoing the need to establish subsidiaries or branches in the countries they operate in. As a result of this, businesses are able to separate the location of the activities that generate economic value from the physical location of the customer. This creates tax challenges as businesses are able to manipulate their operations such that their 'core business activities' are performed in low tax jurisdictions. Base erosion and profit shifting (BEPS) has been on the agenda for a number of years as countries have become increasingly concerned about profits being shifted to other jurisdictions. At the request of the G20 leaders in 2013, the Organisation for Economic Co-operation and Development (OECD) prepared a 15 point action plan in order to address such concerns. The final version of the report was released in September 2015.Action Plan 1 of the report deals specifically with the tax challenges raised by the digital economy. The report states that the recommendations in the report in its entirety will address BEPS risks, but specifically that Action Plan 7 will serve to mitigate any risks introduced by the digital economy.